Kebijakan Pemerintah Kota Padang dalam Pengembangan Pariwisata Berbasis Kearifan Lokal - M. Fedro Syafiola; Bob Alfiandi; Indraddin Indraddin (Universitas Batanghari Jambi, 2023)
Padang city government policy in the development of local wisdom-based tourism is an effort to strengthen and promote local wisdom as the main attraction in tourism in the city of Padang. In this study, a qualitative approach was used with data collection techniques through interviews, observations, and document studies. The results showed that the Padang city government policy in the development of tourism based on local wisdom has succeeded in increasing the number of tourists and tourism revenue in the city of Padang. The policy also encourages the participation of local communities in the management and development of tourism, so as to improve the welfare of local communities. However, there are still some obstacles in the implementation of these policies, such as lack of coordination between relevant agencies and lack of public awareness of the importance of maintaining local wisdom. Therefore, there is a need for further efforts to improve coordination between Related Agencies and provide education to the public about the importance of maintaining local wisdom in tourism development in Padang.In addition, in the development of tourism based on local wisdom, the Padang City Government has also established several programs and policies that are implemented in an integrated manner. The Program includes the development of tourist villages, revitalization of existing tourist attractions, and training to the community related to local wisdom and handicrafts.